2021
DOI: 10.1111/jcmm.16604
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin alleviates liver injury in sepsis through Nrf2‐mediated NF‐κB signalling suppression

Abstract: Sepsis is a life‐threatening organ dysfunction syndrome, and liver is a susceptible target organ in sepsis, because the activation of inflammatory pathways contributes to septic liver injury. Oxidative stress has been documented to participate in septic liver injury, because it not only directly induces oxidative genotoxicity, but also exacerbates inflammatory pathways to potentiate damage of liver. Therefore, to ameliorate oxidative stress is promising for protecting liver in sepsis. Wogonin is the compound e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Clinical studies show that cell death mechanisms are a promising therapeutic approach for treating liver diseases. However, further research needs to elucidate the relationship between the different cell death mechanisms in hepatocytes to understand the pathological machinery of liver diseases (Dai et al 2021 ). Concluding, the diversity of the described pathway in the context of cell death yields various targets for possible targeted therapies.…”
Section: Main Textmentioning
confidence: 99%
“…Clinical studies show that cell death mechanisms are a promising therapeutic approach for treating liver diseases. However, further research needs to elucidate the relationship between the different cell death mechanisms in hepatocytes to understand the pathological machinery of liver diseases (Dai et al 2021 ). Concluding, the diversity of the described pathway in the context of cell death yields various targets for possible targeted therapies.…”
Section: Main Textmentioning
confidence: 99%
“…ROS can lead to host genetic mutation and inflammation, consequently causing liver injury [ 59 ]. In the progression of sepsis, the generation of ROS is closely linked to the occurrence and development of liver damage, not only via the direct damage to hepatocytes by promoting the formation of oxidative protein adducts and lipid peroxides but also through the proinflammatory response accentuated by oxidative stress [ 7 ]. In fact, as the main metabolic organ responsible for deoxygenation, lipid synthesis, and glycogen storage, the liver is more vulnerable to oxidative stress induced by a variety of factors, including sepsis-associated inflammatory responses [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that oxidative stress is a common mechanism of sepsis-induced liver injury. It not only directly leads to genotoxic damage (DNA damage) but also exacerbates the inflammatory pathway to amplify the injury of hepatocytes [ 7 ]. Oxidative stress is regarded as an imbalance between reactive oxygen species (ROS) production and elimination by antioxidant systems [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress also promoted the release of proinflammatory factors in hepatocytes and Kupffer cells, and induced infiltration of neutrophils and lymphocytes to augment the liver damage [16]. Suppression of oxidative stress and inflammation ameliorated septic liver damage [17]. βeudesmol reduced hydrogen peroxide-induced inflammation and oxidative stress in dermal fibroblasts [9].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB, essential for the secretion of proinflammatory factors, was activated in cecal ligation and puncture-induced septic rats [18]. Inhibition of NF-κB signaling attenuated cecal ligation and puncture-induced septic liver injury [17]. β-eudesmol suppressed the activation of NF-κB signaling in hydrogen peroxide-induced dermal fibroblasts in order to reduce inflammation and oxidative stress [9].…”
Section: Discussionmentioning
confidence: 99%